Sobre la captura del regulador y el injusto penal de colusión - Guimaray Mori, Erick (2015)
The State delegates the provision of an important number of services of general interest for society, and the State delegates them to private economic operators. However, in these circumstances the need for regulation in order to achieve allocative efficiency underlies as a duty of the State.In this article, the author presents how the criminal offence of collusion is a way of regulatory capture, and how it brings along negative consequences for the social welfare and progress. The author also reaches a conclusion concerning which is the legal right protected with the aforementioned crime.